Promising Change, Delivering Continuity: REDD+ as Conservation Fad. (January 2017) - Lund, Jens Friis; Sungusia, Eliezeri; Mabele, Mathew Bukhi; Scheba, Andreas
Highlights: We analyze forest policy change in Tanzania over three decades. We cover two forest policy epochs: Participatory Forest Management (PFM) and REDD+. Both forest policy epochs feature initial enthusiasm and substantial donor financing. Neither policy has achieved much beyond policy development and pilot projects. We re-conceptualize REDD+ as both conservation fad and green grab. Summary: REDD+ is an ambition to reduce carbon emissions from deforestation and forest degradation in the Global South. This ambition has generated unprecedented commitment of political support and financial funds for the forest-development sector. Many academics and people-centered advocacy organizations have conceptualized REDD+ as an example of "green grabbing" and have voiced fears of a potential global rush for land and trees. In this paper we argue that, in practice and up until now, REDD+ resembles longstanding dynamics of the development and conservation industry, where the promise of change becomes a discursive commodity that is constantly reproduced and used to generate value and appropriate financial resources. We thus argue for a re-conceptualization of REDD+ as a conservation fad within the broader political economy of development and conservation. We derive this argument from a study that compares the emergence of REDD+ in Tanzania with that of a previous forest-policy model called Participatory Forest Management. Our study describes how the advent of REDD+ implies change at the discursive level, but also continuity and repetitiveness in terms of the initial promises and expectations leading to substantial donor financing, pilot project activities, and policy development and implementation processes. In both epochs, these have achieved little in terms of changing actual forest management and use on the ground outside selected pilot project sites, but have sustained the livelihoods of actors within the development and conservation industry, including academics. Given that there are still many who look to REDD+ in the hope of addressing global climate change, despite less than hoped for financial support at the global level, our study provides an important starting point for questioning the uses of the finances for REDD+ that are actually amassed.